Risk factors associated with mortality in methanol-exposed patients at a public hospital in Lima, Peru - Zegarra Piérola, Jaime (2025)
Methanol poisoning is a neuro-metabolic emergency that can cause severe metabolic acidosis, cerebral dysfunction, and death. Objective: To describe the factors associated with mortality in patients with methanol poisoning treated at a general hospital in Lima, Peru. Methods: A descriptive, case series study was conducted. It included patients admitted to the Intensive Care Unit of Hospital Nacional Cayetano Heredia with cerebral dysfunction and hyperlactatemia after ingesting the alcoholic beverage "Punto D Oro," between September and October 2022. Results: Thirteen patients were evaluated; 10 were male (77%), with an average age of  39 ± 6,96 years and a duration of illness of  3,5 ± 2,4 hours; 100% presented with blurred vision and altered sensorium; 81% had abdominal pain. The average APACHE II score was 19,5 ± 4,98 and the SOFA score was 11,3 ± 2,17; systolic blood pressure was  118,3 ± 20,70 mm Hg, diastolic blood pressure 66,1 ± 9,49 mm Hg, heart rate  107,5 ± 28,04 beats/min, respiratory rate  25,1 ± 5,39 breaths/min, and Glasgow Coma Scale (GCS) score was 9 (range 4–15). Lactate was  8,8 ± 3,88 mmol/L; pH 6,8 ± 0,16;   HCO₃⁻ 4,8 ± 1,33 mEq/L; anion gap 38,6 ± 7,81. The overall mortality was 23.07%. Factors associated with higher mortality were: lower Glasgow Coma Scale score (p=0.009), higher SOFA score (p=0.04), elevated lactate (p=0.017), and low bicarbonate on the third day (p = 0.042). Conclusion: Mortality was 23.07% and was significantly related to greater neurological severity, greater organ dysfunction, and more severe metabolic acidosis.